Konversionen in Rom in der Frühen Neuzeit das Ospizio dei Convertendi 1673 - 1750 - Matheus, Ricarda 1971- (Bibliothek des Deutschen Historischen Instituts in Rom, 2012)
"During the Early Modern Period, thousands of Protestants converted to Roman Catholicism in Rome. Based on numerous unpublished Vatican sources, the author examines the institutional, political, and religious aspects of this phenomenon. She also explores the fate of those who converted. This multi-perspectival approach shows the history of conversions as a fruitful field of research for examining elements of cultural contact as well as associated processes of exchange and adaptation." --Summary from Angus & Robertson website, accessed 11 Jan. 2013